2023
DOI: 10.1108/rpj-09-2022-0332
|View full text |Cite
|
Sign up to set email alerts
|

Study of unidirectional torsion of samples with different internal structures manufactured in the MEX process

Abstract: Purpose Manufacturing of products loaded with torque in an incremental process should take into account the strength in relation to the internal structure of the details. Incremental processes allow for obtaining various internal structures, both in the production process itself and as a result of designing a three-dimensional computer-aided design model with programmable strength. Finite element analysis (FEA) is often used in the modeling process, especially in the area of topological optimization. There is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This is an important issue because these connections are indirectly responsible for the correct operation of, for example, gear transmissions [6]. The research performed concerned the analysis of spline connections manufactured using Fused Filament Fabrication (FFF) and PolyJet technologies [7][8][9]. PLA and RGD720 photopolymer resin materials were used for the manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important issue because these connections are indirectly responsible for the correct operation of, for example, gear transmissions [6]. The research performed concerned the analysis of spline connections manufactured using Fused Filament Fabrication (FFF) and PolyJet technologies [7][8][9]. PLA and RGD720 photopolymer resin materials were used for the manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested statistical techniques to optimize the parameters for enhancing the FDM parts quality in terms of the desired response. Budzik et al (2023) [11] presented the influence of specimen's internal structure printed in material extrusion (MEX) technique on the selected parameters. The FEA of the spline connection was performed by the procedure of unidirectional torsion of samples with various internal structures, and the results were compared with the test of unidirectional torsion of the connection.…”
Section: Introductionmentioning
confidence: 99%
“…Material extrusion (MEX) technologies are rapidly developing due to their congruence with widely used thermoplastic polymers in commerce, ease of implementation, and general availability [10,11]. Hence, they are increasingly used in commercial, research, and hobby sectors for manufacturing machine components and developing functional engineering prototypes and systems [12,13].…”
mentioning
confidence: 99%